Studi Tingkat Loyalitas Konsumen Hotel XX di Jakarta Barat - Fransisca, Angeline; Thalia, Ria; Abdillah, Fitri; Oktarianto, Felix (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2024)
Hotel XX Jakarta is four-star hotels offering a variety of luxuries and conveniences for guests. Problems that occur in hotels that are the number of hotels that have been built that causes guests have many options to stay. That's where we want to examine the level of customer loyalty Hotel XX Jakarta. Due to the many hotels that become rivals, how Hotel XX Jakarta can still stand up to this time. In this research, we distributed questionnaires online. The results we get from the responses of consumers in the questionnaire, states that the services provided is good enough. The implication of this high service quality is that the respondent's loyalty is also high. In order to maintain this performance, more varied services are needed.